Multi-Varied Realities Of Malay Cultural Identities In Popular Tv Fiction - Mohd Muzhafar Idrus; Hazleena Baharun; Noor Saazai Mat Saad; Suzanah Selamat; Ruzy Suliza Hashim; Raihanah M. M; Harison Mohd Sidek; Yurni Emilia Abdul Hamid (OCERINT International Organization Center of Academic Research, 2024)
Indexed by WOS